2002
DOI: 10.1097/00007632-200209150-00015
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Study of the Outcomes of the Surgical Treatment Of Adolescent Idiopathic Scoliosis Using the Scoliosis Research Society (SRS) Outcome Instrument

Abstract: Preoperative pain exists in our adolescent scoliosis population. Pain scores were improved in our study population at the 2-year postsurgical follow-up. Statistically significant improvements were likewise seen in the General Self-Image, Function From Back Condition, and Level of Activity domains. The present study demonstrates the ability of surgery to improve the outcome of patients afflicted with adolescent idiopathic scoliosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
77
1
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(91 citation statements)
references
References 13 publications
9
77
1
4
Order By: Relevance
“…When the questionnaire is applied both preoperatively and postoperatively, the changes in domains like self-image, pain, function, and mental status can also be evaluated. Merola et al in a multicenter study of seven different institutions reported an average score of 3.68/5.00 at 24 months and the improvements in the scores were statistically significant [31]. There are also studies on different scoring types and the unique questionnaires developed for each country and languages [5][6][7]10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the questionnaire is applied both preoperatively and postoperatively, the changes in domains like self-image, pain, function, and mental status can also be evaluated. Merola et al in a multicenter study of seven different institutions reported an average score of 3.68/5.00 at 24 months and the improvements in the scores were statistically significant [31]. There are also studies on different scoring types and the unique questionnaires developed for each country and languages [5][6][7]10].…”
Section: Discussionmentioning
confidence: 99%
“…These studies also report that Harrington rod system has comparable clinical and radiological results with the modern instrumentation systems, however, the final deformitycorrection rates are very small and the overall lifequality at the last follow-up visit is almost unchanged when compared with the third-generation instrumentation systems [17,21,23,24,26,31,32,47]. Long-term results with the modern systems are limited [5,21,23,26,29,33].…”
Section: Introductionmentioning
confidence: 92%
“…Previous studies have demonstrated that the lumbar curve is the most reliable predictor of self-image: A large pretreatment curve correlates to negative patient satisfaction and low total SRS outcome score [22]. However, the degree of curve correction does not appear to correlate significantly with the outcome [21,23].…”
mentioning
confidence: 95%
“…The Scoliosis Research Society instrument for outcome assessment (SRS 24) was designed to measure outcome after surgery, particularly in adolescent idiopathic scoliosis (AIS) patients [19][20][21].…”
mentioning
confidence: 99%
See 1 more Smart Citation